A NIR‐II Photoactivatable “ROS Bomb” with High‐Density Cu2O‐Supported MoS2 Nanoflowers for Anticancer Therapy - Jia Huang; Guiming Deng; Shuya Wang; Tianjiao Zhao; Qiaohui Chen; Yuqi Yang; Yongqi Yang; Jinping Zhang; Yayun Nan; Zhaoqian Liu; Ke Cao; Qiong Huang; et al. (Advanced Science, 2023)
Abstract The fast conversion of hydrogen peroxide (H2O2) into reactive oxygen species (ROS) at tumor sites is a promising anticancer strategy by manipulating nanomedicines with near‐infrared light in the second region (NIR‐II). However, this strategy is greatly compromised by the powerful antioxidant capacity of tumors and the limited ROS generation rate of nanomedicines. This dilemma mainly stems from the lack of an effective synthesis method to support high‐density copper‐based nanocatalysts on the surface of photothermal nanomaterials. Herein, a multifunctional nanoplatform (MCPQZ) with high–density cuprous (Cu2O) supported molybdenum disulfide (MoS2) nanoflowers (MC NFs) is developed for the efficient killing of tumors via a potent ROS storm by an innovative method. Under NIR‐II light irradiation, the ROS intensity and maximum reaction velocity (Vmax) produced by MC NFs are 21.6 and 33.8 times that of the non–irradiation group in vitro, which is much higher than most current nanomedicines. Moreover, the strong ROS storm in cancer cells is efficiently formed by MCPQZ (increased by 27.8 times compared to the control), thanks to the fact that MCPQZ effectively pre–weakens the multiple antioxidant systems of cancer cells. This work provides a novel insight to solve the bottleneck of ROS‐based cancer therapy.